SYSTEMATIC LITERATURE REVIEW: PENERAPAN E-GOVERMENT DALAM MENINGKATKAN PELAYANAN PUBLIK - Syamsuddin, Syamsuddin; Nawir, Adi; Adiputra, Muhlis Hajar; Wahid, Abd; Hatta, Sukarno (Jurnal Academia Praja, 2025)
This research is to analyze the application of e-government in improving public services. The research method used is systematic literature review (SLR) using the Scopus data base. A total of 271 articles sourced from scopus accounts. The results showed that the application of e-government has had a significant impact on the quality of public services, although there are variations in success in various countries. It can be seen that the UK is the highest country in discussing E-Goverment in improving public services. with 39 articles from 2020 to 2024. The main supporting factors include government commitment, adequate technology infrastructure, digital innovation, and employee competence. However, challenges such as lack of socialization, limited infrastructure, and low synergy between institutions still need to be addressed. The optimization strategies include strengthening technological infrastructure, improving public education, developing responsive policies, and service innovation to ensure the sustainability and effectiveness of e-government across countries. lanjutan dan efektivitas e-government di seluruh negara